Structural insights into 1,4-bis(neopentyloxy)pillar[5]arene and the pyridine host–guest system - Mickey Vinodh; Fatemeh H. Alipour; Talal F. Al-Azemi (IUCrData, 2024)
The crystal structure of 1,4-bis(neopentyloxy)pillar[5]arene, C95H140N2O10 (TbuP), featuring two encapsulated pyridine molecules, reveals significant host–guest interactions. Interestingly, the pyridine guests are positioned near the neopentyloxy substituents instead of the electron-rich aromatic core of the pillar[5]arene. This spatial arrangement suggests a preference for the pyridine molecules to engage with the aliphatic regions of the host. Detailed analysis of the structural characteristics of this host–guest system (TbuP·2Py), as well as its packing pattern within the crystal network, is presented and discussed.